Discovering bisdemethoxycurcumin from curcuma longa rhizome as a potent small molecule inhibitor of human pancreatic alpha-amylase, a target for type-2 diabetes - Ponnusamy, Sudha; Smita S. Zinjarde; Bhargava, Shobha; Rajamohanan, P. R.; RaviKumar, Ameeta (Food Chemistry, 2012)
Curcuma longa rhizome is used extensively in culinary preparations in Far East and South-East Asia. Health benefits of curcuminoids from C. longa as antioxidants, anti-cancer and anti-inflammatory molecules have been well documented. We report here for the first time that Bisdemethoxycurcumin (BDMC) from C. longa, acts as an inhibitor to inactivate human pancreatic alpha-amylase, a therapeutic target for oral hypoglycemic agents in type-2 diabetes. Bioactivity guided isolation of rhizome isopropanol extract led to the identification by HPLC and NMR of BDMC as a lead small molecule inhibitor of porcine and human pancreatic alpha-amylase with an IC50 value of 0.026 and 0.025 mM, respectively. Kinetic analysis revealed that using starch as the substrate, HPA exhibited an uncompetitive mode of inhibition with an apparent K-i of 3.0 mu M. The study gains importance as BDMC could be a good drug candidate in development of new inhibitors of HPA and of functional foods for controlling starch digestion in order to reduce post-prandial hyperglycemia. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: BDMC; Curcuma longa; Human pancreatic amylase; kinetics; Type-2 diabetes

Conversion of dried aspergillus candidus mycelia grown on waste whey to biodiesel by in situ acid transesterification - Kakkad, Hardik; Khot, Mahesh; Smita S. Zinjarde; RaviKumar, Ameeta; Kumar, V. Ravi; Kulkarni, B. D. (Bioresource Technology, 2015)
This study reports optimization of the transesterification reaction step on dried biomass of an oleaginous fungus Aspergillus candidus grown on agro-dairy waste, whey. Acid catalyzed transesterification was performed and variables affecting esterification, viz., catalyst methanol and chloroform concentrations, temperature, time, and biomass were investigated. Statistical optimization of the transesterification reaction using Plackett-Burman Design showed biomass to be the predominant factor with a 12.5-fold increase in total FAME from 25.6 to 320 mg. Studies indicate that the transesterification efficiency in terms of conversion is favored by employing lower biomass loadings. A. candidus exhibited FAME profiles containing desirable saturated (30.2%), monounsaturated (31.5%) and polyunsaturated methyl esters (38.3%). The predicted and experimentally determined biodiesel properties (density, kinematic viscosity, iodine value, cetane number, TAN, water content, total and free glycerol) were in accordance with international (ASTM D6751, EN 14214) and national (IS 15607) standards. (C) 2015 Published by Elsevier Ltd.
Keywords: Aspergillus candidus; Biodiesel; In situ acid transesterification; Plackett-Burman Design; Whey

Gedunin and azadiradione: human pancreatic alpha-amylase inhibiting limonoids from neem (azadirachta indica) as anti-diabetic agents - Ponnusamy, Sudha; Haldar, Saikat; Mulani, Fayaj A.; Smita S. Zinjarde; Thulasiram, Hirekodathakallu; RaviKumar, Ameeta (Plos One, 2015)
Human pancreatic alpha-amylase (HPA) inhibitors offer an effective strategy to lower postprandial hyperglycemia via control of starch breakdown. Limonoids from Azadirachta indica known for their therapeutic potential were screened for pancreatic alpha-amylase inhibition, a known anti-diabetic target. Studies were carried out to reveal their mode of action so as to justify their hypoglycemic potential. Of the nine limonoids isolated/semi-synthesized from A. indica and screened for alpha-amylase inhibition, azadiradione and exhibited potential inhibition with an IC50 value of 74.17 and 68.38 mu M, respectively against HPA under in vitro conditions. Further screening on AR42J alpha-amylase secretory cell line for cytotoxicity and bioactivity revealed that azadiradione and gedunin exhibited cytotoxicity with IC50 of 11.1 and 13.4 mu M. Maximal secreted alpha-amylase inhibition of 41.8% and 53.4% was seen at 3.5 and 3.3 mu M, respectively. Michaelis-Menten kinetics suggested a mixed mode of inhibition with maltopentaose (K-i 42.2, 18.6 mu M) and starch (K-i' 75.8, 37.4 mu M) as substrate with a stiochiometry of 1: 1 for both azadiradione and gedunin, respectively. The molecular docking simulation indicated plausible p-alkyl and alkyl-alkyl interactions between the aromatic amino acids and inhibitors. Fluorescence and CD confirmed the involvement of tryptophan and tyrosine in ligand binding to HPA. Thermodynamic parameters suggested that binding is enthalpically and entropically driven with Delta G degrees of -21.25 kJ mol(-1) and -21.16 kJ mol(-1) for azadiradione and gedunin, respectively. Thus, the limonoids azadiradione and gedunin could bind and inactivate HPA (anti-diabetic target) and may prove to be lead drug candidates to reduce/control post-prandial hyperglycemia.

Role of aliasing and interacting factors in the enhanced production of dehalogenase from Yarrowia lipolytica for degradation of brominated compounds - Vatsal, Aakanksha; Potdar, Chirag; Smita S. Zinjarde; Kumar, V. Ravi; Kulkarni, Bhasker D.; RaviKumar, Ameeta (Journal of Industrial and Engineering Chemistry, 2016)
Use of persistent organobromines for industrial applications has led to their accumulation in environment. Yarrowia lipolytica NCIM 3589, a tropical marine yeast, degrades and detoxifies bromocompounds by an initial hydrolytic step. By optimizing culture conditions with 1-bromodecane as reference compound, the dehalogenase involved was remarkably enhanced 13-fold (384.13 U/ml) by a hybrid statistical Plackett-Burman and Box-Behnken design of experiments. Studies bring out in a novel way the role of aliasing and other masked interactions in growth media factors. Importantly, the enzyme acted on C3-C16 bromoalkanes and bromoaromatics, thereby generalizing the 'green chemistry' applicability of optimized media formulation for biotechnological applications. (C) 2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.

Optimization of the in situ transesterification step for biodiesel production using biomass of Yarrowia lipolytica NCIM 3589 grown on waste cooking oil - Katre, Gouri; Raskar, Shubham; Zinjarde, Smita; Kumar, V. Ravi; Kulkarni, B. D.; RaviKumar, Ameeta (Energy, 2018)
The in situ (one-step) acid-catalyzed transesterification step for conversion to biodiesel of biomass from oleaginous yeast Yarrowia lipolytica grown on waste cooking oil (WCO) is studied. The process yield of biodiesel was optimized by investigating effects of various parameters, namely, biomass, methanol, chloroform, catalyst, temperature, time and sonication. A Plackett-Burman statistical design of experiments revealed that biomass is the most significant factor influencing biodiesel (FAME, fatty acid methyl ester) production. Subsequently, a one variable design (OVD) of experiments for increased biomass loadings showed higher yields of FAME with no additional requirement of reactants, solvents or special equipment. The biomass grown on WCO had a lipid productivity of 0.042 g L-1 h(-1) and 4 g of this loading gave a high FAME yield of 0.88 gin 8 hat 50 degrees C with methanol: chloroform (10:1) and acid catalyst (0.2 M H2SO4,1.0 ml g(-1)). The FAME profile had desirable amounts of saturated (32.81%), monounsaturated (36.41%), polyunsaturated (30.59%) methyl esters. The predicted and experimentally determined physico-chemical properties of FAME were found in accordance with specified international standards. Thus, the direct one-pot in situ transesterification reaction using Y. lipolytica biomass grown on WCO provides a high yield of biodiesel with potential applicability while simultaneously addressing the management of this pollutant. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; FAME; In situ transesterification; One -step; Waste cooking oil; Yarrowia lipolytica

Biodegradation of squalene and n-hexadecane by Gordonia amicalis HS-11 with concomitant formation of biosurfactant and carotenoids - Sowani, Harshada; Deshpande, Ashish; Gupta, Vidya; Kulkarni, Mohan; Zinjarde, Smita (International Biodeterioration & Biodegradation, 2019)
Gordonia amicalis HS-11 has been enriched from a hydrocarbon contaminated tropical soil sample. The ability of this organism to utilize a triterpenic polyunsaturated hydrocarbon, squalene (2,6,10,15,19,23-hexamethyl-6,6,10,14,18,20-tetracosahexane) and the model saturated hydrocarbon n-hexadecane is described here. The isolate degraded squalene and n-hexadecane (79 +/- 3.02 and 96 +/- 4.11%, respectively) after eight days of incubation. The isolate produced an extracellular biosurfactant that reduced surface tension from 69 +/- 2.83 to 40 +/- 1.63 and 35 +/- 2.34 mN m(-1) with squalene and n-hexadecane as carbon sources, respectively, after 6 days. The Actinomycete cleaved squalene to geranylacetone and famesyl acetaldehyde that were further utilized for supporting growth. n-Hexadecane was degraded via monoterminal oxidation and activities of important enzymes (alkane hydroxylase and alcohol dehydrogenase) were highest (215 +/- 8.76 and 169 +/- 6.02 units mg(-1) protein, respectively) after four days. Cells grown on squalene were short and with n-hexadecane there were clumps of longer cells. Squalene and n-hexadecane-grown cell surfaces were smooth possibly due to extracellular surface active compounds. While growing on hydrophobic substrates, some cells were seen adhering to droplets and others were in the free form. The culture was able to simultaneously degrade hydrocarbons and produce two commercially relevant value-added products. The yield of the extracellular biosurfactant on n-hexadecane was 480 mg l(-1) and cells grown on squalene and n-hexadecane also yielded carotenoids (2.3 +/- 0.14 and 2.9 +/- 0.10 mg g(-1) dry cell weight, respectively). This is the first report on the utilization of squalene by Gordonia.
Keywords: Aerobic biodegradation; Carotenoids; Catabolic pathways; Emulsifier; Gordonia amicalis HS-11